NUEVOS REGISTROS PARA LA FLORA DE CHILE: MAGALLANA PORIFOLIA CAV. (TROPAEOLACEAE), TRISTAGMA AMEGHINOI (SPEG.) SPEG. Y TRISTAGMA PATAGONICUM (BAKER) TRAUB (ALLIACEAE) - Faúndez Y., Luis; Macaya B., Jorge H. (Gayana Botánica, 2000)
Magallana porifolia Cav., Tristagma ameghinoi (Speg.) Speg. and Tristagma patagonicum (Baker) Traub, are reported for first time for the chilean flora, growing in the Region of Aysen (Region XI). The species are described and comments about their habitats are made.